Biographical dictionary of women's movements and feminisms in Central, Eastern, and South Eastern Europe : 19th and 20th centuries - Daskalova, Krasimira; Haan, Francisca de, 1957-; Loutfi, Anna (Central European University Press, 2005)
This Biographical Dictionary describes the lives, works and aspirations of more than 150 women and men who were active in, or part of, women's movements and feminisms in Central, Eastern and South Eastern Europe. Thus, it challenges the widely held belief that there was no historical feminism in this part of Europe. These innovative and often moving biographical portraits not only show that feminists existed here, but also that they were widespread and diverse, and included Romanian princesses, Serbian philosophers and peasants, Latvian and Slovakian novelists, Albanian teachers, Hungarian Christian social workers and activists of the Catholic women's movement, Austrian factory workers, Bulgarian feminist scientists and socialist feminists, Russian radicals, philanthropists, militant suffragists and Bolshevik activists, prominent writers and philosophers of the Ottoman era, as well as Turkish republican leftist political activists and nationalists, internationally recognized Greek feminist leaders, Estonian pharmacologists and science historians, Slovenian 'literary feminists,' Czech avant-garde painters, Ukrainian feminist scholars, Polish and Czech Senate Members, and many more. Their stories together constitute a rich tapestry of feminist activity and redress a serious imbalance in the historiography of women's movements and feminisms.